2019
DOI: 10.1001/jamanetworkopen.2019.12200
|View full text |Cite
|
Sign up to set email alerts
|

Association of Optimism With Cardiovascular Events and All-Cause Mortality

Abstract: This meta-analysis assesses whether individuals with a mindset of optimism have a lower risk of cardiovascular events and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 62 publications
5
104
0
8
Order By: Relevance
“…There are reported associations with coronary heart disease 3 , 4 , stroke 5 , all-cause mortality 6 , 7 , or all-cause mortality with sub-division into grouped causes of death 8 10 . A recent meta-analysis 11 confirmed these associations. In general, more optimistic people have longer survival than more pessimistic people.…”
Section: Introductionmentioning
confidence: 85%
“…There are reported associations with coronary heart disease 3 , 4 , stroke 5 , all-cause mortality 6 , 7 , or all-cause mortality with sub-division into grouped causes of death 8 10 . A recent meta-analysis 11 confirmed these associations. In general, more optimistic people have longer survival than more pessimistic people.…”
Section: Introductionmentioning
confidence: 85%
“…However, considering premature mortality risk, an objective endpoint, offers some methodological strengths such as virtually no misclassification and research based on longitudinal design by nature of the outcome. Recent meta-analyses have suggested that life satisfaction, positive affect, meaning/purpose in life, and optimism are protective against premature mortality [3436], though the quality of statistical adjustment for potential confounders in these studies was variable. Here, we briefly discuss evidence as to whether and how various PWB dimensions are prospectively associated with premature all-cause mortality, specifically.…”
Section: Psychological Well-being and Mortalitymentioning
confidence: 99%
“…For example, for heart patients, depression increases risk for slower recovery and early mortality ( Gathright et al, 2017 ). High optimism, the most studied positive asset, is linked to fewer cardiac events and lower mortality across studies of heart disease patients, controlling for depression ( DuBois et al, 2015 ; Rozanski et al, 2019 ).…”
Section: Stress Resilience and Reserve Capacitymentioning
confidence: 99%